2015
DOI: 10.1002/ett.2969
|View full text |Cite
|
Sign up to set email alerts
|

Merging of DHT‐based logical networks in MANETs

Abstract: We study the challenging problem of the network partitioning and merging in context with the mismatch problem and the resilience of the logical structure in distributed hash table (DHT)-based routing protocols for mobile ad hoc networks (MANETs). The existing DHT-based approaches for routing in MANETs do not consider the merging of logical networks, which occurs because of limited transmission range and mobility of nodes. In this paper, we identify that the mismatch problem is aggravated when logical networks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…The research attempting to use the DHT in MANET can be grouped according to four perspectives as; efficient routing [58]- [61], data transmission [62], [63], handling the dynamic topology [64]- [66] and mitigation of the traffic overhead [67].…”
Section: Dht Applications In Manetmentioning
confidence: 99%
See 3 more Smart Citations
“…The research attempting to use the DHT in MANET can be grouped according to four perspectives as; efficient routing [58]- [61], data transmission [62], [63], handling the dynamic topology [64]- [66] and mitigation of the traffic overhead [67].…”
Section: Dht Applications In Manetmentioning
confidence: 99%
“…Due to the limited transmission range and self-organizing nature of MANET, network partitioning and merging can happen frequently. The DHT is leveraged to keep the relation between the logical and physical address of nodes in [58]- [61] to solve the network partitioning and merging. Through the simulation-based evaluation, it has been shown that DHTassisted network partitioning and merging is beneficial in terms of achieving efficient and scalable routing in MANET.…”
Section: Routingmentioning
confidence: 99%
See 2 more Smart Citations
“…Data routing and traffic control are the core of WANETs. Recent studies proved that the DHT-based routing protocols (e.g., 3D-RP [4][5], M-DART [6], VCP [7], Motion-MX [8], 3DcRP [9], and LA-3D-IS [10]) are better in performance compared to the traditional routing protocols, which use flooding in the route discovery phase (e.g., AODV [11], OLSR [12], and DYMO [13]). The DHT-based routing mechanism [14] avoids/reduces the network-wide flooding in the route discovery phase, thus increasing the scalability in WANETs.…”
Section: Introductionmentioning
confidence: 99%